The Influence of Audio Visual Based Learning in Improving Student Learning Outcomes in Elementary Schools - Eriawaty, Eriawaty; Rokhmah, Siti; Aljauhari, Shofwan (Al-Mudarris, 2025)
Audio-visual-based learning has become the object of discourse, especially those that focus on discussing development, utilization, and application in the learning process, so discourse regarding the influence of audio-visual-based learning in improving student learning outcomes tends to be neglected in scientific discussions. In line with this, this study focuses on "How is the influence of audio-visual based learning in improving student learning outcomes". This study uses a quantitative approach by conducting observations and test-based testing on teachers and students. The test was carried out twice before and after audio-visual-based learning was implemented. The test results are used to determine student learning outcomes, so that it can be seen whether there is an influence in the implementation of audio-visual based learning. The findings in this study show that the application of audio-visual based learning not only increases teacher activity in the learning process by 92.64% but is also able to increase student learning outcomes by 82.35%. Audio-visual based learning has been proven to be an effective method that improves student learning outcomes.